Strategies For Increasing Self-Initiated Verbal Interaction - Securro, Samuel, Jr.; Walls, Richard T.; West Virginia Univ., Morgantown ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
The purpose of this study was to determine if behavior recording strategies in a field setting would increase the verbal responsiveness of prospective teachers participating in informal, small group discussions. The sample consisted of 192 male and female undergraduate education majors enrolled in an introductory educational psychology course. Subjects were randomly assigned to 12 discussion groups and to three treatments. The three treatment conditions used were: a) the student recorded his own talking behavior, b) the discussion leader recorded the subject's talking behavior with the subject's knowledge, and c) the control condition in which responses were recorded by the instructor with the student's knowledge. All groups met weekly for one 50 minute discussion period. Following the 4-week treatment period, subjects that had averaged four or more responses for the first and second recording sessions were eliminated from the statistical analysis. The remaining 120 subjects were identified as "passive" and only for these subjects were the analyses performed. Results indicated that recording strategies can increase the level of verbal responsiveness for passive students under the conditions described. A 9-item bibliography is included. (MJM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Education Majors; Responses; Student Behavior; Student Participation; Student Reaction; Verbal Communication